ВЫРАЖЕНИЕ ДИДАКТИЧЕСКИХ ИГР В НАЧАЛЬНОМ ОБРАЗОВАНИИ ЧЕРЕЗ ЦИФРОВЫЕ ТЕХНОЛОГИИ - Ярашов Мардон Джобирович (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Helping elementary school students to concentrate their thoughts by involving them in a 1-hour lesson increases their level of mastery. The use of various games in the educational process increases the student's interest. This article talks about didactic games that can be used in the course of the lesson and how to give them through digital technologies.